(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2026)
The evaluation of Air Pollution Tolerance Index (APTI) and Anticipated Performance Index (API) for trees is of paramount importance given the increasing severity of air pollution on the environment. It is worth noting that different plant species react and adapt differently to air pollutants rely on the environmental conditions of their planting site, thus plant species can be used as important bio-monitors for air pollution. Therefore, this study was useful for monitoring air quality and identifying suitable sensitive and tolerant plant species that can be planted to control air pollution or used as bio-monitors, which could form an important mechanism for reducing air pollution in various polluted environments. This study was conducted on Tecoma, Oleander, and Sidr trees in two areas in Brack Al-Shati; namely the university site and Ashkadah area, where the tolerance index of these plants to air pollutants was estimated by analyzing four parameters: the pH of the leaf extract, relative water content, total chlorophyll, and ascorbic acid concentration, in addition to evaluating the anticipated performance index. The study results revealed that the tolerance of the studied trees ranged from moderately tolerant (Immediately Tolerant) to tolerant. The results proved that the Sidr tree was the best tolerant tree to air pollutants in both study sites, while Tecoma trees ranged between moderate and tolerant tolerance in the study area. The API results confirmed that Sidr gave excellent performance, followed by Oleander, then Tecoma. One-Way ANOVA was conducted to evaluate the effect of different treatments on some of the studied biochemical traits, and the correlation results showed that the APTI index exhibited a strong positive correlation (p < 0.01) with both total chlorophyll (0.735) and ascorbic acid (0.989). A weak negative correlation was observed between relative water content and pH with the air pollution tolerance index.